THE MOST IMPRESSIVE BOOK I HAVE EVER READ - Isroiljon qizi G.X; Abdumoʼminova Noila (TADQIQOTLAR, 2025)
Abstract This article expresses my reaction as a reader to the book called "The mountain is you" written by Brianna Wiest who is famous female writer from United States of America. Additionally, it provides reasons why this masterpiece had a good impression on me and what triggered me to read it as well as whom I recommend this book.